A kind of anti-corrosion packaging film and preparation method thereof
By modifying the layered double hydroxide compound (LDH) and filling it in the packaging film of the photovoltaic module, the corrosion problem of offshore photovoltaic modules in high salt spray and high humidity environments is solved, and higher corrosion resistance and weather resistance are achieved.
Patent Information
- Application Number
- CN202411164125.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-08-23
AI Technical Summary
Offshore photovoltaic modules are susceptible to chloride ion corrosion in high salt spray and high humidity environments, resulting in reduced battery power and aging and peeling of packaging films, affecting the reliability of the components.
The layered dihydroxide compound (LDH) is modified by a silane coupling agent to make the surface hydrophobic, reduce moisture absorption, and regulate the interlayer anions by hydrothermal method to prepare LDH of the anion interlayer, and fill it in the adhesive film to extend the diffusion path of chloride ions.
Improves the production stability, light transmittance and bonding stability of the adhesive film, enhances the corrosion resistance to chloride ions, extends the service life of the components, and improves weather resistance in high salt spray environments at sea.
Smart Images

Figure CN118667477B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of encapsulation films for solar cell modules, and in particular to an encapsulation film for offshore photovoltaic modules and a preparation method thereof. Background Art
[0002] The high salt fog environment on the sea surface will cause a large number of chloride ions to invade the surface of the battery cell along the gaps in the auxiliary materials, causing serious corrosion of the battery and a significant reduction in power. The long-term humid environment will also cause the encapsulation film in the photovoltaic module to age and peel off, affecting the photovoltaic module's photoelectric conversion efficiency and overall reliability. Therefore, modifying the function of the photovoltaic encapsulation film to enhance its weather resistance to adapt to the harsh environment of high salt fog and high humidity at sea has become a key step in the development of offshore photovoltaic modules.
[0003] Patent CN116694262A discloses a high refractive index packaging film and its preparation method and application. In the present invention, by designing the components of the high refractive index packaging film and further using modified nano-silicon dioxide, the refractive index of the packaging film is increased, and the transmittance of the incident light is increased. The photovoltaic module prepared in this way has a high photoelectric conversion efficiency. However, in terms of corrosion resistance, it cannot adapt to the harsh environment of high salt fog and high humidity at sea.
[0004] Patent CN118222197A discloses a composite adhesive film for Topcon solar cells and its preparation method and application. The composite adhesive film for Topcon solar cells has two outer layers as acid-absorbing adhesive layers. By modifying hydrotalcite, the free acid generated externally or internally can be adsorbed without affecting the transmittance, ensuring that the cell is not corroded by acidic substances; by modifying silane and silane oligomers, the composite adhesive film maintains a high adhesion under hot and humid conditions; the middle layer improves the crosslinking density by adding ethylene-modified resin and cooperating with acrylate to improve the water barrier of the composite adhesive film and prevent the intrusion of water vapor. This scheme uses hydrotalcite as an acid scavenger to neutralize the acetic acid generated during the hot and humid aging of the EVA film, but the LDH surface contains a large number of carboxyl groups and has a large hydrophilicity. A large amount of water enriched on the LDH surface is easy to accelerate the hydrolysis of EVA acetic acid, which is counterproductive. In addition, the active agent groups on the surface of LDH are prone to agglomeration and poor dispersion, which can easily produce crystal points and holes during the extrusion process of the film and affect the light transmittance of the film. Therefore, untreated LDH is not suitable for direct addition into the encapsulation film. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a corrosion-resistant encapsulation adhesive film and a preparation method thereof. LDH is modified by a silane coupling agent, and the silane coupling agent with a hydrophobic group reacts to remove the active hydroxyl groups on the surface of LDH.
[0006] On the one hand, the hydrophilicity of LDH is transformed into hydrophobicity, reducing the absorption of water and improving the agglomeration of LDH; on the other hand, the type of anions between LDH layers is regulated by the hydrothermal method to prepare LDHs with different anion intercalations. The LDHs filled in the film have a "maze effect" and can greatly extend the diffusion path of small molecules and chloride ions.
[0007] In order to achieve the above object, the present invention adopts the following technical solutions:
[0008] The invention provides an anti-corrosion encapsulation adhesive film, comprising 0-100 parts by weight of a base resin, 0-50 parts by weight of a modified masterbatch, 0.1-2 parts by weight of a peroxide crosslinking agent, 0.1-2 parts by weight of an auxiliary crosslinking agent, 0.1-2 parts by weight of a coupling agent, 0.1-2 parts by weight of a coupling agent oligomer, and 0.01-1 parts by weight of a light stabilizer, wherein the modified masterbatch is prepared from a layered double hydroxide (LDH) and an inorganic sodium salt by a silane coupling agent hydrothermal method, and the weight ratio of the layered double hydroxide (LDH), the inorganic sodium salt, and the silane coupling agent is 2:1:20;
[0009] The modified masterbatch is a double hydroxide compound intercalated with anions [M2 + 1-xM 3+ x(OH)2][A n- ] x / n mH2O;
[0010] The double hydroxide of anion intercalation is at least one of nitrate anion intercalation, sulfate anion intercalation, hydroxide anion intercalation, phosphate anion intercalation, vanadate anion intercalation, and molybdate anion intercalation.
[0011] The anti-corrosion encapsulation film is characterized in that the preparation method of the modified masterbatch comprises:
[0012] Step 1: 200 parts by weight of conventional (double hydroxide) LDH and 100 parts by weight of inorganic sodium salt are mixed and dissolved in 200 parts by weight of deionized water to prepare a solution, which is placed in a three-necked flask heated in a water bath at 65°C and stirred vigorously for 24 hours;
[0013] Step 2: then adding the prepared solution into a reactor, reacting at 125°C and 100 MPa for 24 hours, filtering and precipitating the obtained solution, and drying the water to prepare anion intercalated double hydroxide (LDH);
[0014] Step 3: 4 parts by weight of the double hydroxide (LDH) prepared by the hydrothermal reaction above, 100 parts by weight of a film resin and 10 parts by weight of a silane coupling agent are mixed and stirred evenly, and then melt-extruded and granulated at a temperature range of 80°C-160°C to obtain a modified masterbatch.
[0015] The inorganic sodium salt is one or more of sodium hydroxide, sodium nitrate, sodium chloride, sodium carbonate, sodium sulfate, sodium phosphate, sodium vanadate, and sodium molybdate.
[0016] The film matrix resin is one or more of EVA (ethylene-vinyl acetate copolymer), POE (ethylene-olefin copolymer), PVB (polyvinyl butyral), PVDF (polyvinylidene fluoride), PVA (polyvinyl alcohol), and PVF (polyvinyl fluoride).
[0017] The peroxide crosslinking agent comprises one or more of tert-butyl peroxycarbonate-2-ethylhexyl, tert-amyl peroxy (2-ethylhexyl) carbonate, tert-butyl peroxybenzoate, tert-butyl peroxyacetate, tert-amyl peroxy-2-ethylhexanoate, tert-butyl peroxy-2-ethylhexanoate, and dicumyl peroxide.
[0018] The auxiliary cross-linking agent comprises one or more of triallyl isocyanurate, trimethylolpropane trimethacrylate, trimethylolpropane triacrylate, trimethylolpropane triethoxyacrylate, triallyl isocyanate, ethoxylated trimethylolpropane triacrylate, propoxylated glycerol triacrylate, 4-functional polyester acrylate, and 1,6-hexanediol diacrylate.
[0019] The coupling agent comprises one or more of vinyl trimethoxy silane, vinyl triethoxy silane, vinyl tri(β-methoxyethoxy) silane, γ-methacryloxypropyl trimethoxy silane and vinyl tri-tert-butoxy silane, which are compounded in a certain proportion.
[0020] The coupling agent oligomer includes one or more of vinyl coupling agent oligomer, diamino coupling agent oligomer, epoxy coupling agent oligomer, alkoxy coupling agent oligomer and methacryloxy coupling agent oligomer.
[0021] The light stabilizer is a hindered amine light stabilizer, including one or more of bis-2,2,6,6-tetramethylpiperidinol sebacate, polysuccinic acid (4-hydroxy-2,2,6,6-tetramethyl-1-piperidinethanol) ester, and bis (2,2,6,6-tetramethyl-4-piperidinol) sebacate.
[0022] Furthermore, the anti-corrosion packaging film is composed of a single layer or a multi-layer composite.
[0023] A method for preparing a corrosion-resistant packaging film comprises the following steps:
[0024] Step 1: Mix the base resin, modified masterbatch, oxide crosslinking agent, auxiliary crosslinking agent, coupling agent, coupling agent oligomer, and light stabilizer components in a mixing stirring kettle at 40-50° C. for 3-6 hours to allow the added additives to be fully absorbed into the resin masterbatch;
[0025] Step 2: The mixed masterbatch is put into a single-screw extruder casting machine and, according to conventional process parameters, melt-plasticized extrusion, casting, embossing, cooling, pulling, and winding to obtain a single-layer or double-layer composite film with uniform thickness;
[0026] Furthermore, the thickness of the corrosion-resistant packaging film is 0.20-0.80 mm.
[0027] The beneficial effects of the present invention are:
[0028] By modifying the surface of LDH additives, improving their agglomeration and hydrophilicity, LDH additives are evenly dispersed in the film, with strong bonding and good compatibility with the film segments, strengthening the "maze effect" of LDH flake materials, extending the diffusion path of water vapor and chloride ions, and enhancing the production stability, light transmittance and bonding stability of the film;
[0029] By regulating the anions between the LDH additive layers, the exchange efficiency of the LDH material for chloride ions is improved, the concentration of chloride ions on the battery surface is reduced, and anions with corrosion inhibition effects are released. The metal corrosion inhibitor can react with the metal on the surface of the battery cell to form a dense oxide film covering the metal surface, further preventing the invasion of corrosive substances into the battery cell, providing long-term and effective adhesion and corrosion resistance for component packaging, reducing the power attenuation of the component, and increasing the weather resistance of the film in the high salt fog environment at sea. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 :Schematic diagram of the invasion route of corrosive substances.
[0031] Figure 2 : Schematic diagram of the anti-corrosion mechanism of vanadate intercalated LDH.
[0032] In the figure: 1 photovoltaic glass, 2 anti-corrosion film, 3 corrosion-resistant layer, 4 battery cell, 5 corrosion substance invasion route, 6 anion intercalated double hydroxide. DETAILED DESCRIPTION
[0033] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the present invention will be clearly and completely described in combination with the embodiments below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] The beneficial effects of the present application will be further illustrated below in combination with embodiments and comparative examples.
[0035] Example 1
[0036] The modified masterbatch provided by the invention is prepared from layered double hydroxide (LDH) and inorganic sodium salt by a silane coupling agent hydrothermal method.
[0037] The preparation method of modified double hydroxide (LDH) masterbatch comprises:
[0038] Step 1: Take 200 parts by weight of conventional (double hydroxide) LDH and 100 parts by weight of sodium nitrate, mix and dissolve in 200 parts by weight of deionized water, prepare a solution and place it in a three-necked flask heated in a 65°C water bath, and stir vigorously for 24 hours;
[0039] Step 2: then adding the prepared solution into a reactor, reacting at 125° C. and 100 MPa for 24 h, filtering and precipitating the prepared solution, and drying the water to prepare a nitrate anion intercalation layer;
[0040] Step 3: Mix 4 parts by weight of the double hydroxide (LDH) prepared by the hydrothermal reaction, 100 parts by weight of POE resin and 10 parts by weight of γ-methacryloxypropyltrimethoxysilane, stir evenly, and then melt-extrude and granulate at a temperature range of 80°C-160°C to obtain a POE modified masterbatch.
[0041] The present invention provides an anti-corrosion encapsulation adhesive film and a preparation method thereof, comprising 100 parts by weight of POE resin, 20 parts by weight of LDH modified masterbatch, 0.8 parts by weight of tert-butyl peroxycarbonate-2-ethylhexyl ester, 0.6 parts by weight of triallyl isocyanurate, 0.4 parts by weight of γ-methacryloxypropyl trimethoxysilane, 0.1 parts by weight of vinyl silane oligomer, and 0.2 parts by weight of bis-2,2,6,6-tetramethylpiperidinol sebate;
[0042] Step 1: Mix the base resin, modified masterbatch, oxide crosslinking agent, auxiliary crosslinking agent, coupling agent, coupling agent oligomer, and light stabilizer components in a mixing stirring kettle at 40-50° C. for 3-6 hours to allow the added additives to be fully absorbed into the resin masterbatch;
[0043] Step 2: The mixed masterbatch is put into a single-screw extruder casting machine and is melt-plasticized, extruded, cast, embossed, cooled, pulled and rolled to form a packaging film with a thickness of 0.6 mm according to conventional process parameters.
[0044] Example 2
[0045] The present embodiment differs from the embodiment 1 in that the inorganic sodium salt is sodium sulfate and LDH is sulfate anion intercalation.
[0046] Example 3
[0047] The difference between this embodiment and embodiment 1 is that the inorganic sodium salt is sodium hydroxide and LDH is a hydroxide anion intercalation.
[0048] Example 4
[0049] The present embodiment differs from the embodiment 1 in that the inorganic sodium salt is sodium phosphate and LDH is the phosphate anion intercalation layer.
[0050] Example 5
[0051] The present embodiment differs from the embodiment 1 in that the inorganic sodium salt is sodium vanadate and LDH is a vanadate anion intercalation layer.
[0052] Example 6
[0053] The present embodiment differs from the embodiment 1 in that the inorganic sodium salt is sodium molybdate and LDH is a molybdate anion intercalation layer.
[0054] Example 7
[0055] The difference between this embodiment and embodiment 1 is that the amount of LDH modified masterbatch is 10 parts by weight.
[0056] Example 8
[0057] The difference between this embodiment and embodiment 1 is that the amount of LDH modified masterbatch is 30 parts by weight.
[0058] Comparative Example 1
[0059] The difference between this comparative example and implementation 1 is the preparation method of the modified double hydroxide (LDH) masterbatch:
[0060] Step 3: Mix 4 parts by weight of the double hydroxide (LDH) prepared by the hydrothermal reaction, 100 parts by weight of EVA resin and 10 parts by weight of γ-methacryloxypropyltrimethoxysilane, stir evenly, and then melt-extrude and granulate at a temperature range of 80°C-160°C to obtain EVA modified masterbatch.
[0061] The invention provides an anti-corrosion encapsulation adhesive film and a preparation method thereof, comprising 100 parts by weight of EVA resin, 20 parts by weight of LDH modified masterbatch, 0.8 parts by weight of tert-butyl peroxycarbonate-2-ethylhexyl ester, 0.6 parts by weight of triallyl isocyanurate, 0.4 parts by weight of γ-methacryloxypropyl trimethoxysilane, 0.1 parts by weight of vinyl silane oligomer, and 0.2 parts by weight of bis-2,2,6,6-tetramethylpiperidinol sebate.
[0062] Step 1: Mix the base resin, modified masterbatch, oxide crosslinking agent, auxiliary crosslinking agent, coupling agent, coupling agent oligomer, and light stabilizer components in a mixing stirring kettle at 40-50° C. for 3-6 hours to allow the added additives to be fully absorbed into the resin masterbatch;
[0063] Step 2: The mixed masterbatch is put into a single-screw extruder casting machine and is melt-plasticized, extruded, cast, embossed, cooled, pulled and rolled to form a packaging film with a thickness of 0.6 mm according to conventional process parameters.
[0064] Comparative Example 2
[0065] The invention provides an anti-corrosion packaging adhesive film and a preparation method thereof. The anti-corrosion packaging adhesive film comprises the following components in parts by weight: 100 parts by weight of EVA resin, 0.1 parts by weight of conventional LDH, 0.8 parts by weight of tert-butyl peroxycarbonate-2-ethylhexyl ester, 0.6 parts by weight of triallyl isocyanurate, 0.4 parts by weight of γ-methacryloxypropyl trimethoxysilane, 0.1 parts by weight of vinyl silane oligomer, and 0.2 parts by weight of bis-2,2,6,6-tetramethylpiperidinol sebate. The components are stirred and mixed in a mixing kettle at 40-50 DEG C, so that the added auxiliary agent is fully absorbed into the resin master batch; then the master batch is put into an extruder and, according to conventional process parameter conditions, melt-plasticized extrusion, casting, embossing, cooling, pulling, and winding are performed to form a packaging adhesive film with a thickness of 0.6 mm.
[0066] Comparative Example 3
[0067] The invention provides an anti-corrosion encapsulation adhesive film and a preparation method thereof. The anti-corrosion encapsulation adhesive film comprises the following components in parts by weight: 100 parts by weight of POE resin, 0.1 parts by weight of conventional LDH, 0.8 parts by weight of tert-butyl peroxycarbonate-2-ethylhexyl ester, 0.6 parts by weight of triallyl isocyanurate, 0.4 parts by weight of γ-methacryloxypropyl trimethoxysilane, 0.1 parts by weight of vinyl silane oligomer, and 0.2 parts by weight of bis-2,2,6,6-tetramethylpiperidinol sebate. The components are stirred and mixed in a mixing kettle at 40-50 DEG C to allow the added auxiliary agent to be fully absorbed into a resin master batch; then the master batch is put into an extruder and, according to conventional process parameter conditions, melt-plasticized extrusion, casting, embossing, cooling, pulling, and winding are performed to form an encapsulation adhesive film with a thickness of 0.6 mm.
[0068] Comparative Example 4
[0069] The invention provides an anti-corrosion packaging adhesive film and a preparation method thereof. The components in parts by weight consist of: 100 parts by weight of POE resin, 0.1 parts by weight of modified nano silicon dioxide, 0.8 parts by weight of tert-butyl peroxycarbonate-2-ethylhexyl ester, 0.6 parts by weight of triallyl isocyanurate, 0.4 parts by weight of γ-methacryloxypropyl trimethoxysilane, 0.1 parts by weight of vinyl silane oligomer, and 0.2 parts by weight of bis-2,2,6,6-tetramethylpiperidinol sebate. The components are stirred and mixed in a mixing kettle at 40-50° C. so that the added auxiliary agent is fully absorbed into the resin master batch; then the master batch is put into an extruder and, according to conventional process parameter conditions, melt-plasticized extrusion, casting, embossing, cooling, pulling, and winding are performed to form a packaging adhesive film with a thickness of 0.6 mm.
[0070] The properties of the anti-corrosion packaging films prepared in the above examples and comparative examples were tested, and the results are shown in Table 1.
[0071] Transmittance: Measured in accordance with ISO 9050-2003.
[0072] Peel Strength:
[0073] Initial peel strength with glass
[0074] The test method refers to the national standard GB / T2790 "Adhesive 180° Peel Strength Test Method Flexible Material to Rigid Material". Preparation of the peel strength sample of the packaging film and the battery: Take 2.0mm embossed glass, battery, packaging film, and backplane, heat and laminate them to make the sample to be tested, the lamination parameters are 148℃, and the air is pumped for 6 minutes.
[0075] DH2000+ peel strength with glass after 500H salt spray test
[0076] First, make the peel strength sample between the packaging film and the battery.
[0077] The conditions of the salt spray test are: temperature 35°C, humidity 95%, salt spray deposition rate 2.0 (80 cm2·h), and pH value 6.5-7.2; the samples are placed in a dry heat oven at 150°C for 24 h and a high temperature and high humidity (DH) aging oven for 2000 h, and then the corresponding peel strength tests are carried out.
[0078] Power attenuation after DH 2000+ salt spray test for 500 hours
[0079] The packaging film was used to carry out the packaging test of the single glass module. The glass / packaging material (polyurethane adhesive layer attached to the cell) / cell / packaging film (polyolefin matrix layer attached to the backplane) / backplane were placed in the vacuum laminator in the order of glass / packaging material (polyurethane adhesive layer attached to the cell) / cell / packaging film (polyolefin matrix layer attached to the backplane) / backplane. The lamination parameters were 148°C vacuum for 6 min, pressurization for 1 min, and pressure maintenance for 12 min. After light activation, the initial power of the module was tested using the IV test system, and then the module was placed in the DH aging box for 2000 h of aging test. After the test, the power of the module after aging was tested using the IV test system, and the power attenuation result of the module was known by calculation.
[0080] Table 1 Performance test data of examples and comparative examples
[0081]
[0082] It can be seen from the data in the table.
[0083] From Examples 1\2\3\4, it can be seen that the exchange efficiency of nitrate-intercalated LDH for chloride ions is higher, and the peel strength with glass after DH 2000+ salt spray test for 500 H is greater than 65 N, which is greatly improved compared with Comparative Example 1.
[0084] From Examples 5\6, it can be seen that LDH intercalated with vanadate and molybdate has the best corrosion resistance. This is attributed to the fact that LDH can not only absorb chloride ions to reduce the concentration of chloride ions on the battery surface, but also release vanadate and molybdate anions with corrosion inhibition effects. Vanadate and molybdate can react with the metal on the surface of the battery cell to form a dense oxide film covering the metal surface, further preventing corrosive substances from invading the battery cell.
[0085] It can be seen from Example 7 that too little addition of LDH will affect the corrosion resistance of the film.
[0086] It can be seen from Example 8 that excessive addition of LDH will affect the light transmittance of the film.
[0087] From Comparative Example 1, it can be seen that the weather resistance of POE film is better than that of EVA film.
[0088] From comparative examples 2\3, the "maze effect" of LDH effectively prolongs the diffusion path of water vapor and chloride ions, and provides certain protection for the battery cells; from other data, the anti-corrosion encapsulation film and preparation method proposed in Example 1 have a simple process flow and take into account both low cost and high reliability.
[0089] The modified nano-silica added in Comparative Example 4 only improves the transparency of the film, but the peel strength and power attenuation performance are not good, and the weather resistance is relatively poor and cannot adapt to the harsh environment of high salt fog and high humidity at sea.
[0090] The raw materials and equipment used in the present invention, unless otherwise specified, are all commonly used raw materials and equipment in the art; the methods used in the present invention, unless otherwise specified, are all conventional methods in the art.
[0091] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any way. Any simple modification, change and equivalent transformation made to the above embodiment based on the technical essence of the present invention still falls within the protection scope of the technical solution of the present invention.
Claims
1. A corrosion-resistant encapsulation film, comprising 100 parts by weight of POE resin, 20 parts by weight of modified masterbatch, 0.8 parts by weight of tert-butyl peroxycarbonate-2-ethylhexyl ester, 0.6 parts by weight of triallyl isocyanurate, 0.4 parts by weight of γ-methacryloxypropyltrimethoxysilane, 0.1 parts by weight of vinyl silane oligomer, and 0.2 parts by weight of bis-2,2,6,6-tetramethylpiperidinol sebate; characterized in that The modified masterbatch is prepared from layered double hydroxide and inorganic sodium salt by a silane coupling agent hydrothermal method, and the preparation method of the modified masterbatch comprises: Step 1: 200 parts by weight of layered double hydroxide and 100 parts by weight of inorganic sodium salt are mixed and dissolved in 200 parts by weight of deionized water to prepare a solution, which is placed in a three-necked flask heated in a 65° C. water bath and stirred vigorously for 24 hours; Step 2: adding the prepared solution into a reaction kettle, reacting at 125° C. and 100 MPa for 24 h, filtering and precipitating the obtained solution, and drying the water to prepare an anion intercalated double hydroxide; Step 3: 4 parts by weight of the double hydroxide prepared by the hydrothermal reaction, 100 parts by weight of POE resin and 10 parts by weight of silane coupling agent are mixed and stirred evenly, and then melt-extruded and granulated at a temperature range of 80° C.-160° C. to obtain a modified masterbatch; The weight ratio of the layered double hydroxide, the inorganic sodium salt and the silane coupling agent is 2:1:20; The modified masterbatch is a double hydroxide compound intercalated with anions [M 2+ 1-xM 3+ x(OH)2][A n- ] x / n mH2O; the double hydroxide of the anion intercalation is at least one of vanadate anion intercalation or molybdate anion intercalation; The inorganic sodium salt is one or more of sodium vanadate and sodium molybdate.
2. A method for preparing the anti-corrosion packaging film according to claim 1, comprising the following steps: Step 1: POE resin, modified masterbatch, tert-butyl peroxycarbonate-2-ethylhexyl ester, triallyl isocyanurate, γ-methacryloxypropyl trimethoxysilane, vinyl silane oligomer, and bis-2,2,6,6-tetramethylpiperidinol sebate components are mixed in a mixing stirring kettle at 40-50° C. for 3-6 hours to allow the added additives to be fully absorbed into the resin masterbatch; Step 2: The mixed masterbatch is put into a single-screw extruder casting machine and, according to conventional process parameters, melt-plasticized extrusion, casting, embossing, cooling, pulling and winding are performed to obtain a single-layer or double-layer composite film with uniform thickness. The thickness of the corrosion-resistant encapsulation film is 0.6 mm.
Citation Information
Patent Citations
Anticorrosive layered double-hydroxy composite metal hydroxide film and preparation method thereof
CN102634835A
Preparation method of corrosion inhibitor composite anion intercalated hydrotalcite
CN111348666A
Blended EVA-EAA-PVB packaging adhesive film as well as preparation method and application thereof
CN116445095A